Effect of Taro Starch-Hydrocolloids Mixture as a Functional Ingredient on the Quality of Milk Dessert - Feroz Alam; Anjum Nawab; Tanveer Abbas; Mohib Kazimi; Abid Hasnain (Journal of Basic & Applied Sciences, 2015)
The study was carried out to investigate the effect of taro starch-hydrocolloids mixture on the physical and sensory properties of milk dessert. Four different hydrocolloid i.e. arabic, Carboxymethyl cellulose (CMC), guar and xanthan gums were mixed with taro starch in different concentration and their potential use in milk dessert as functional ingredients were evaluated. Physical and sensory characteristics were found to be considerably improved in different aspects by adding these functional ingredients. Taro starch-arabic gum blend was observed to be an effective additive to produce creamy texture of milk dessert. Syneresis from dessert was noted to be diminished and sensory characteristics were also found to be improved by adding taro starch-guar gum blend. Similarly, taro starch-xanthan gum blend has effectively been stabilized the texture and sensory properties of milk dessert.